A low-brittle glass substrate and its preparation process
By special treatment of silica and titanium dioxide and preparing glass substrates in combination with float process, the problem of reduced brittleness of light and thin glass substrates is solved, and high alkali resistance, chemical stability and low brittleness are achieved.
Patent Information
- Application Number
- CN202411805562.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, when producing thinner glass substrates, the brittleness is severely reduced, making it difficult to take into account the alkali resistance, chemical stability and brittleness of the glass substrate.
By special treatment of a portion of the silica, combined with specially treated titanium dioxide, as the raw material component of the glass substrate, the glass substrate is prepared by a float process, and the molding temperature and outlet temperature are controlled to reduce the brittleness of the glass substrate.
It achieves the improvement of alkali resistance and chemical stability of the glass substrate while reducing its brittleness, and has excellent mechanical properties, chemical resistance and thermal properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a low-brittleness glass substrate and a preparation process thereof, belonging to the field of glass substrate preparation. Background Art
[0002] TFT-LCD glass substrate is the core component of the liquid crystal display panel. It is a thin glass sheet with an extremely flat surface and a key strategic material for the electronic information display industry. Its core technology has long been monopolized by a few foreign companies. In recent years, China has become the third country to master the production technology of high-generation TFT-LCD glass substrates, and my country's glass substrate industry has also ushered in a dawn.
[0003] The properties of ultra-thin flat glass substrates mainly depend on the composition of their raw material components, which will affect the glass's thermal expansion coefficient, viscosity, chemical resistance, optical transmittance and absorption, and electrical properties. In addition to the composition of the raw material components, the production method of the glass substrate will also have a great impact on its performance.
[0004] So far, there are three methods for producing TFT-LCD glass substrates, namely the float method, the flow hole draw method, and the overflow melting method. Among them, the "float method" has scratches and bumps on the surface due to the need to extend horizontally in the tin bath during the preparation process. The surface needs to be ground to obtain a glass substrate with a smooth surface, but it can produce glass products with a larger width and has the advantage of larger production capacity; the glass substrate produced by the "overflow melting method" has excellent surface properties and does not need to be ground to eliminate surface defects. In addition, the preparation process is relatively simple and is more suitable for the production of ultra-thin flat glass with a thickness of less than 2mm. However, the width of the produced glass is limited to less than 1.5 meters, and the production capacity is therefore relatively small; in order to avoid warping of the glass substrate during the annealing process, the "flow hole draw method" needs to be annealed in the vertical direction, which will greatly increase the cost.
[0005] CN117105526A discloses a highly stable and long-life substrate glass for liquid crystal display, which has good alkali resistance and chemical stability, and improves the service life of the substrate glass for liquid crystal display. The invention adopts a float process, which can reduce the surface defects of the glass substrate and improve the alkali resistance and chemical stability of the glass substrate. However, the thickness of the produced glass substrate is relatively large, and the minimum thickness of the produced glass substrate is only 0.7mm. In addition, the brittleness of the glass substrate produced by this method is relatively large. If this method is used to produce a thinner glass substrate, the brittleness reduction will be more serious.
[0006] In summary, the existing technology of producing glass substrates using the float process can produce glass substrates with a relatively flat surface and good alkali resistance and chemical stability, but the glass substrates are relatively brittle, and the decrease in brittleness is particularly serious when producing lighter and thinner glass substrates. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects of the prior art. By specially treating a part of silicon dioxide and combining it with specially treated titanium dioxide as a raw material component of a glass substrate, a thinner glass substrate is produced, thereby improving the alkali resistance and chemical stability of the glass substrate and reducing the brittleness of the glass substrate.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A low-brittle glass substrate, the raw material components of the glass substrate include base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, cerium oxide, and the mass ratio of the components is 550-650:75-125:20-30:30-35:15-19:25-35:25-35:4-6.
[0010] The following are further improvements to the above technical solution:
[0011] The purity of the matrix silicon dioxide is 99.79wt%, the iron content is 27ppm, the particle size is 35μm, and the specific surface area is 334m 2 / g;
[0012] The preparation method of the amine-treated silica is as follows:
[0013] The heating rate is controlled to be 4.5-5.5°C / min, the temperature is raised to 725-775°C, the silicon dioxide is calcined for 350-370 minutes, and after the calcination is completed, it is naturally cooled to 68-72°C and kept warm for use, and the calcined silicon dioxide kept at 68-72°C is added to 68-72°C methanol in a sealed container, stirred to mix evenly, and then branched polyethyleneimine is added, the temperature is maintained at 68-72°C, and stirred for 23-25 hours. After the stirring is completed, the sealed container is opened, the temperature is raised to 74-76°C, the methanol is evaporated, and the silicon dioxide with surface amino treatment is obtained;
[0014] The mass ratio of silicon dioxide, methanol and branched polyethyleneimine is 45-55:100-120:0.9-1.1;
[0015] The silicon dioxide has a purity of 99.79 wt%, an iron content of 27 ppm, a particle size of 20 μm, and a specific surface area of 327 m 2 / g;
[0016] The weight average molecular weight of the branched polyethyleneimine is 12700-13600 g / mol.
[0017] The preparation method of the modified titanium dioxide comprises treating 3-aminopropyltriethoxysilane with polyglycolic acid, and modifying;
[0018] The method for treating 3-aminopropyltriethoxysilane with polyglycolic acid is as follows:
[0019] Mixing polyglycolic acid with acetone to completely dissolve the polyglycolic acid solution, adjusting the pH of the polyglycolic acid solution to 2.3-2.5 with acetic acid, then adding 3-aminopropyltriethoxysilane, controlling the temperature to 1-3°C, stirring, maintaining the pH at 5.4-5.6 during stirring, stirring for 50-70 minutes, evaporating the solvent after the stirring, adding the obtained solid product to a sodium hydrosulfide aqueous solution, stirring for 40-50 minutes, filtering, washing, and drying the product after the stirring, and obtaining polyglycolic acid-treated 3-aminopropyltriethoxysilane;
[0020] The mass ratio of the polyglycolic acid, acetone and 3-aminopropyltriethoxysilane is 4.5-5.5:75-125:24-30;
[0021] The mass ratio of the solid product to the sodium hydrosulfide aqueous solution is 1:4.5-5.5;
[0022] The concentration of the sodium hydrosulfide aqueous solution is 4.5-5.5wt%.
[0023] The modification method is:
[0024] The titanium dioxide is uniformly dispersed in anhydrous ethanol, and then 3-aminopropyltriethoxysilane treated with polyglycolic acid is added, and the pH is adjusted to 3.6-3.8 with hydrochloric acid, and the temperature is controlled to 62-67° C. The stirring is performed for 4.5-5.5 hours. After the stirring is completed, the modified titanium dioxide is obtained by suction filtration, washing, and drying.
[0025] The mass ratio of titanium dioxide, anhydrous ethanol, and polyglycolic acid-treated 3-aminopropyltriethoxysilane is 8-12:125-175:0.9-1.1;
[0026] The particle size of the titanium dioxide is 70 μm.
[0027] The preparation method of the glass substrate is as follows:
[0028] The glass substrate is prepared by using a float process, wherein a specified mass of base silica, surface amino-treated silica, alumina, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide are mixed to ensure that each component is evenly mixed, and the temperature is controlled to be 1520-1570° C. for melting, and the molten glass liquid is passed through a tin bath, and the molding temperature in the tin bath is controlled to be 825-875° C., and the outlet temperature of the tin bath is controlled to be 630-650° C. for float molding, and after molding, the glass substrate is taken out of the tin bath, annealed, and finally surface polished to obtain a glass substrate;
[0029] The thickness of the glass substrate is 0.5 mm and the density is 2.33-2.34 g / cm 3 .
[0030] Compared with the prior art, the present invention achieves the following beneficial effects:
[0031] The glass substrate of the present invention has low brittleness. The Vickers hardness of the glass substrate is tested according to the method in GB / T37900-2019, and the fracture toughness of the glass substrate is tested according to the method in GB / T37900-2019, and the ratio of the Vickers hardness to the fracture toughness is used as the brittleness index. The Vickers hardness is 6.65-6.70 GPa, and the fracture toughness is 3.54-3.77 MPa / m 1 / 2 , the brittleness index is 1.78-1.87;
[0032] The glass substrate of the present invention has excellent mechanical properties. According to the method in GB / T34171-2017, the bending strength of the glass substrate is tested, and the bending strength is 938-944 MPa; according to the method in GB / T37788-2019, the elastic modulus of the glass substrate is tested, and the elastic modulus is 81-82 GPa; according to the method in GB / T 39814-2021, the impact strength of the glass substrate is tested, and the impact resistance height is 78-80 mm; according to the method in GB / T 39815-2021, the scratch resistance of the glass substrate is tested, and the critical load force for scratches is 54-56 N;
[0033] The glass substrate of the present invention has excellent chemical resistance. According to the method in SEMI D10-95, the loss of the glass substrate after being etched in different etching solutions is tested. After being etched with 5wt% hydrochloric acid at 95°C for 24 hours, the mass loss is 0.25-0.28mg / cm 2 ; After 24h of 1mol / L nitric acid corrosion at 95℃, the mass loss is 0.14-0.17mg / cm 2 ; After 20h of 10wt% hydrofluoric acid corrosion at 22℃, the mass loss is 2.54-2.71mg / cm 2; After erosion by 5wt% sodium hydroxide at 95℃ for 6h, the mass loss is 0.54-0.66mg / cm 2 ;
[0034] The glass substrate of the present invention has excellent thermal properties, a low expansion coefficient and a high thermal conductivity. According to the method in GB / T16920-2015, the average linear thermal expansion coefficient of the glass substrate is tested; according to the method in GBT38712-2020, the thermal conductivity of the glass substrate is tested, and the average linear thermal expansion coefficient is 4.7-5.0×10 -7 , thermal conductivity is 1.55-1.60W (m·K).
[0035] The glass substrate of the present invention has high transmittance. According to the method in GB / T2680-2021, the visible light transmittance and the total solar energy transmittance are tested, and the visible light transmittance is 98.42-99.02%, and the total solar energy transmittance is 99.04-99.21%. DETAILED DESCRIPTION Example 1
[0036] A low-brittle glass substrate, wherein the raw material components of the glass substrate include base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, and the mass ratio of the components is 600:100:25:35:17:30:30:5;
[0037] The purity of the matrix silicon dioxide is 99.79wt%, the iron content is 27ppm, the particle size is 35μm, and the specific surface area is 334m 2 / g;
[0038] The preparation method of the amine-treated silica is as follows:
[0039] The heating rate is controlled to be 5°C / min, the temperature is raised to 750°C, and the silicon dioxide is calcined for 360 minutes. After the calcination is completed, it is naturally cooled to 70°C and kept warm for use. In a closed container, the calcined silicon dioxide kept at 70°C is added to methanol at 70°C, stirred to mix evenly, and then branched polyethyleneimine is added, the temperature is maintained at 70°C, and stirred for 24 hours. After the stirring is completed, the closed container is opened, the temperature is raised to 75°C, and the methanol is evaporated to obtain silicon dioxide with surface amino treatment;
[0040] The mass ratio of silicon dioxide, methanol and branched polyethyleneimine is 50:110:1;
[0041] The silicon dioxide has a purity of 99.79 wt%, an iron content of 27 ppm, a particle size of 20 μm, and a specific surface area of 327 m 2 / g;
[0042] The weight average molecular weight of the branched polyethyleneimine is 13200 g / mol.
[0043] The preparation method of the modified titanium dioxide comprises treating 3-aminopropyltriethoxysilane with polyglycolic acid, and modifying;
[0044] The method for treating 3-aminopropyltriethoxysilane with polyglycolic acid is as follows:
[0045] Mixing polyglycolic acid with acetone to completely dissolve the polyglycolic acid solution, adjusting the pH of the polyglycolic acid solution to 2.4 with acetic acid, then adding 3-aminopropyltriethoxysilane, controlling the temperature to 2°C, stirring, maintaining the pH at 5.5 during stirring, stirring for 60 minutes, evaporating the solvent after the stirring, adding the obtained solid product to a sodium hydrosulfide aqueous solution, stirring for 45 minutes, filtering, washing, and drying the product after the stirring, and obtaining polyglycolic acid-treated 3-aminopropyltriethoxysilane;
[0046] The mass ratio of the polyglycolic acid, acetone and 3-aminopropyltriethoxysilane is 5:100:27;
[0047] The mass ratio of the solid product to the sodium hydrosulfide aqueous solution is 1:5;
[0048] The concentration of the sodium hydrosulfide aqueous solution is 5wt%.
[0049] The modification method is:
[0050] The titanium dioxide was uniformly dispersed in anhydrous ethanol, and then 3-aminopropyltriethoxysilane treated with polyglycolic acid was added, and the pH was adjusted to 3.7 with hydrochloric acid, and the temperature was controlled to 65° C. The mixture was stirred for 5 hours. After the stirring was completed, the mixture was filtered, washed, and dried to obtain modified titanium dioxide.
[0051] The mass ratio of titanium dioxide, anhydrous ethanol, and polyglycolic acid-treated 3-aminopropyltriethoxysilane is 10:150:1;
[0052] The particle size of the titanium dioxide is 70 μm.
[0053] The preparation method of the glass substrate is as follows:
[0054] The glass substrate is prepared by using a float process, wherein a specified mass of base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide are mixed to ensure that each component is evenly mixed, and the temperature is controlled at 1550° C. to melt the glass, and the molten glass liquid passes through a tin bath, and the molding temperature in the tin bath is controlled at 850° C., and the outlet temperature of the tin bath is controlled at 640° C. to perform float molding, and after molding, the glass substrate is taken out of the tin bath, annealed, and finally surface polished to obtain the glass substrate;
[0055] The thickness of the glass substrate is 0.5 mm and the density is 2.34 g / cm 3 . Example 2
[0056] A low-brittle glass substrate, wherein the raw material components of the glass substrate include base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, and the mass ratio of the components is 550:75:20:30:15:25:25:4;
[0057] The purity of the matrix silicon dioxide is 99.79wt%, the iron content is 27ppm, the particle size is 35μm, and the specific surface area is 334m 2 / g;
[0058] The preparation method of the amine-treated silica is as follows:
[0059] The heating rate was controlled to be 4.5°C / min, and the temperature was raised to 775°C, and the silicon dioxide was calcined for 350 minutes. After the calcination was completed, it was naturally cooled to 68°C and kept warm for use. In a sealed container, the calcined silicon dioxide kept at 68°C was added to methanol at 68°C, and stirred to mix evenly. Then, branched polyethyleneimine was added, and the temperature was kept at 68°C and stirred for 25 hours. After the stirring was completed, the sealed container was opened, and the temperature was raised to 74°C to evaporate the methanol to obtain silicon dioxide with surface amino treatment;
[0060] The mass ratio of silicon dioxide, methanol and branched polyethyleneimine is 45:100:0.9;
[0061] The silicon dioxide has a purity of 99.79 wt%, an iron content of 27 ppm, a particle size of 20 μm, and a specific surface area of 327 m 2 / g;
[0062] The weight average molecular weight of the branched polyethyleneimine is 12700 g / mol.
[0063] The preparation method of the modified titanium dioxide comprises treating 3-aminopropyltriethoxysilane with polyglycolic acid, and modifying;
[0064] The method for treating 3-aminopropyltriethoxysilane with polyglycolic acid is as follows:
[0065] Mixing polyglycolic acid with acetone to completely dissolve the polyglycolic acid solution, adjusting the pH of the polyglycolic acid solution to 2.3 with acetic acid, then adding 3-aminopropyltriethoxysilane, controlling the temperature to 1°C, stirring, maintaining the pH at 5.4 during stirring, stirring for 70 minutes, evaporating the solvent after the stirring, adding the obtained solid product to a sodium hydrosulfide aqueous solution, stirring for 40 minutes, filtering, washing, and drying the product after the stirring, and obtaining polyglycolic acid-treated 3-aminopropyltriethoxysilane;
[0066] The mass ratio of the polyglycolic acid, acetone and 3-aminopropyltriethoxysilane is 4.5:75:24;
[0067] The mass ratio of the solid product to the sodium hydrosulfide aqueous solution is 1:4.5;
[0068] The concentration of the sodium hydrosulfide aqueous solution is 4.5wt%.
[0069] The modification method is:
[0070] Titanium dioxide was uniformly dispersed in anhydrous ethanol, and then polyglycolic acid-treated 3-aminopropyltriethoxysilane was added, and the pH was adjusted to 3.6 with hydrochloric acid, and the temperature was controlled to 62° C. The mixture was stirred for 5.5 hours. After the stirring was completed, the mixture was filtered, washed, and dried to obtain modified titanium dioxide.
[0071] The mass ratio of titanium dioxide, anhydrous ethanol, and polyglycolic acid-treated 3-aminopropyltriethoxysilane is 8:125:0.9;
[0072] The particle size of the titanium dioxide is 70 μm.
[0073] The preparation method of the glass substrate is as follows:
[0074] The glass substrate is prepared by using a float process, wherein a specified mass of base silica, surface amino-treated silica, alumina, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide are mixed to ensure that each component is evenly mixed, and the temperature is controlled at 1520° C. to melt the glass, and the molten glass liquid passes through a tin bath, and the molding temperature in the tin bath is controlled at 825° C., and the outlet temperature of the tin bath is controlled at 630° C. to perform float molding, and after molding, the glass substrate is taken out of the tin bath, annealed, and finally surface polished to obtain the glass substrate;
[0075] The thickness of the glass substrate is 0.5 mm and the density is 2.33 g / cm 3 . Example 3
[0076] A low-brittle glass substrate, wherein the raw material components of the glass substrate include base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, and the mass ratio of the components is 650:125:30:35:19:35:35:6;
[0077] The purity of the matrix silicon dioxide is 99.79wt%, the iron content is 27ppm, the particle size is 35μm, and the specific surface area is 334m 2 / g;
[0078] The preparation method of the amine-treated silica is as follows:
[0079] The heating rate was controlled to be 5.5°C / min, and the temperature was raised to 725°C, and the silicon dioxide was calcined for 370 minutes. After the calcination was completed, it was naturally cooled to 72°C and kept warm for use. In a sealed container, the calcined silicon dioxide kept at 72°C was added to methanol at 72°C, and stirred to mix evenly. Then, branched polyethyleneimine was added, and the temperature was kept at 72°C and stirred for 23 hours. After the stirring was completed, the sealed container was opened, and the temperature was raised to 76°C to evaporate the methanol to obtain silicon dioxide with surface amino treatment;
[0080] The mass ratio of silicon dioxide, methanol and branched polyethyleneimine is 55:120:1.1;
[0081] The silicon dioxide has a purity of 99.79 wt%, an iron content of 27 ppm, a particle size of 20 μm, and a specific surface area of 327 m 2 / g;
[0082] The weight average molecular weight of the branched polyethyleneimine is 13600 g / mol.
[0083] The preparation method of the modified titanium dioxide comprises treating 3-aminopropyltriethoxysilane with polyglycolic acid, and modifying;
[0084] The method for treating 3-aminopropyltriethoxysilane with polyglycolic acid is as follows:
[0085] Mixing polyglycolic acid with acetone to completely dissolve the polyglycolic acid solution, adjusting the pH of the polyglycolic acid solution to 2.5 with acetic acid, then adding 3-aminopropyltriethoxysilane, controlling the temperature to 3°C, stirring, maintaining the pH at 5.6 during stirring, stirring for 50 minutes, evaporating the solvent after the stirring, adding the obtained solid product to a sodium hydrosulfide aqueous solution, stirring for 50 minutes, filtering, washing, and drying the product after the stirring, and obtaining polyglycolic acid-treated 3-aminopropyltriethoxysilane;
[0086] The mass ratio of the polyglycolic acid, acetone and 3-aminopropyltriethoxysilane is 5.5:125:30;
[0087] The mass ratio of the solid product to the sodium hydrosulfide aqueous solution is 1:5.5;
[0088] The concentration of the sodium hydrosulfide aqueous solution is 5.5wt%.
[0089] The modification method is:
[0090] Titanium dioxide was uniformly dispersed in anhydrous ethanol, and then 3-aminopropyltriethoxysilane treated with polyglycolic acid was added, and the pH was adjusted to 3.8 with hydrochloric acid, and the temperature was controlled to 67° C. The mixture was stirred for 4.5 hours. After the stirring was completed, the mixture was filtered, washed, and dried to obtain modified titanium dioxide.
[0091] The mass ratio of titanium dioxide, anhydrous ethanol, and polyglycolic acid-treated 3-aminopropyltriethoxysilane is 12:175:1.1;
[0092] The particle size of the titanium dioxide is 70 μm.
[0093] The preparation method of the glass substrate is as follows:
[0094] The glass substrate is prepared by using a float process, wherein a specified mass of base silica, surface amino-treated silica, alumina, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide are mixed to ensure that each component is evenly mixed, and the temperature is controlled at 1570° C. to melt the glass, and the molten glass liquid passes through a tin bath, and the molding temperature in the tin bath is controlled at 875° C., and the outlet temperature of the tin bath is controlled at 650° C. to perform float molding, and after molding, the glass substrate is taken out of the tin bath, annealed, and finally surface polished to obtain a glass substrate;
[0095] The thickness of the glass substrate is 0.5 mm and the density is 2.33 g / cm 3 .
[0096] Comparative Example 1
[0097] Different from Example 1, in the raw material components, surface amino-treated silica is no longer added as a raw material component, but the same mass of base silica is used instead. The raw material components after replacement include base silica, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, and the mass ratio between the components is 750:25:35:17:30:30:5;
[0098] The remaining steps are the same to prepare the glass substrate.
[0099] Comparative Example 2
[0100] Different from Example 1, in the raw material components, modified titanium dioxide is no longer added as a raw material component, but untreated titanium dioxide of the same mass is used instead, and the raw material components after replacement include matrix silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, and the mass ratio between the components is 650:100:25:35:17:30:30:5;
[0101] The remaining steps are the same to prepare the glass substrate.
[0102] Test Example 1 Glass Substrate Brittleness Test
[0103] The Vickers hardness of the glass substrates of Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T37900-2019, and the fracture toughness of the glass substrates was tested according to the method in GB / T37900-2019, and the ratio of the Vickers hardness to the fracture toughness was used as the brittleness index, and the smaller the value, the lower the brittleness. The results are shown in Table 1.
[0104] Table 1
[0105]
[0106] In Example 1-3, a portion of silicon dioxide is specially treated and used together with specially treated titanium dioxide as a raw material component of the glass substrate to produce a glass substrate with a relatively thin thickness, which can maintain a relatively high hardness and fracture toughness and a relatively low brittleness index;
[0107] In the raw material components of Comparative Example 1, surface amino-treated silica is no longer added as a raw material component, but the same mass of matrix silica is used instead. The untreated silica will cause a more serious decrease in hardness and a certain degree of decrease in fracture toughness, and a higher brittleness index;
[0108] In the raw material components of Comparative Example 2, modified titanium dioxide is no longer added as a raw material component, but untreated titanium dioxide of the same mass is used instead. The untreated titanium dioxide will cause a significant decrease in hardness, a more serious decrease in fracture toughness, and a serious increase in brittleness index.
[0109] Test Example 2 Glass Substrate Mechanical Properties Test
[0110] The glass substrates of Examples 1-3 and Comparative Examples 1-2 were tested for bending strength according to the method in GB / T34171-2017; the elastic modulus of the glass substrates was tested according to the method in GB / T37788-2019; the impact strength of the glass substrates was tested according to the method in GB / T39814-2021, with the impact height of a 32g steel ball damaging the glass substrate as the performance index; the scratch resistance of the glass substrates was tested according to the method in GB / T 39815-2021, with the critical load force for scratches as the performance index;
[0111] The results are shown in Table 2.
[0112] Table 2
[0113]
[0114] In Example 1-3, a portion of silicon dioxide is specially treated and used together with specially treated titanium dioxide as a raw material component of the glass substrate to produce a glass substrate with a relatively thin thickness, and high mechanical properties can be maintained, whether it is bending strength, elastic modulus, impact strength, and scratch resistance, all of which are maintained at a high level;
[0115] In the raw material components of Comparative Example 1, surface amino-treated silica is no longer added as a raw material component, but the same mass of base silica is used instead. Untreated silica will cause a decrease in the mechanical properties of the glass substrate, among which the decrease in bending strength is particularly serious, and the elastic modulus, impact strength, and scratch resistance also decrease to a large extent;
[0116] In the raw material components of Comparative Example 2, modified titanium dioxide is no longer added as a raw material component, but untreated titanium dioxide of the same mass is used instead. Untreated titanium dioxide will cause a decrease in the mechanical properties of the glass substrate, among which the decrease in elastic modulus, impact strength and scratch resistance is particularly serious. In addition, the bending strength decreases to a large extent.
[0117] Test Example 3: Chemical resistance test of glass substrate
[0118] The glass substrates of Examples 1-3 and Comparative Examples 1-2 were tested for loss after being etched in different etching solutions according to the method in SEMI D10-95 to indicate the chemical stability of the glass substrates. The test conditions were set as follows:
[0119] Medium: 5wt% hydrochloric acid; Etching time: 24h; Etching temperature: 95℃;
[0120] Medium: 1mol / L nitric acid; Etching time: 24h; Etching temperature: 95℃;
[0121] Medium: 10wt% hydrofluoric acid; Etching time: 20h; Etching temperature: 22℃;
[0122] Medium: 5wt% sodium hydroxide; Etching time: 6h; Etching temperature: 95℃;
[0123] The mass loss after erosion is shown in Table 3, in mg / cm 2 .
[0124] Table 3
[0125]
[0126] In Example 1-3, a portion of silicon dioxide is specially treated and used together with specially treated titanium dioxide as a raw material component of the glass substrate to produce a glass substrate with a relatively thin thickness, which can maintain a relatively high chemical resistance and a relatively low mass loss in various types of etching solutions;
[0127] In the raw material components of Comparative Example 1, surface amino-treated silica is no longer added as a raw material component, but the same mass of base silica is used instead. Untreated silica will cause the chemical resistance of the glass to decrease, wherein the mass loss in hydrofluoric acid increases seriously, and the mass loss in hydrochloric acid, nitric acid, and sodium hydroxide also increases to a large extent;
[0128] In the raw material components of Comparative Example 2, modified titanium dioxide is no longer added as a raw material component, but untreated titanium dioxide of the same mass is used instead. Untreated titanium dioxide will cause a decrease in the chemical resistance of the glass, wherein the mass loss in hydrochloric acid, nitric acid, and sodium hydroxide increases significantly, and the mass loss in hydrofluoric acid also increases to a large extent.
[0129] Test Example 4 Glass Substrate Thermal Performance Test
[0130] The average linear thermal expansion coefficient of the glass substrates of Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T16920-2015; the thermal conductivity of the glass substrates was tested according to the method in GBT38712-2020. The results are shown in Table 4.
[0131] Table 4
[0132]
[0133] Example 1-3: By specially treating a portion of silicon dioxide and using the specially treated titanium dioxide as a raw material component of the glass substrate, a glass substrate with a thinner thickness is produced, which can maintain good thermal properties, have a lower thermal expansion coefficient and a higher thermal conductivity.
[0134] In the raw material components of Comparative Example 1, surface amino-treated silica is no longer added as a raw material component, but the same mass of matrix silica is used instead. The untreated silica will cause the thermal properties of the glass to decrease, among which the thermal conductivity decreases more seriously, and the thermal expansion coefficient increases to a certain extent;
[0135] In the raw material components of Comparative Example 2, modified titanium dioxide is no longer added as a raw material component, but the same mass of untreated titanium dioxide is used instead. Untreated titanium dioxide will cause a decrease in the thermal properties of the glass, wherein the thermal expansion coefficient increases seriously and the thermal conductivity decreases to a large extent.
[0136] Test Example 5: Optical Performance Test of Glass Substrate
[0137] The glass substrates of Examples 1-3 and Comparative Examples 1-2 were tested for visible light transmittance and total solar energy transmittance according to the method in GB / T2680-2021. The results are shown in Table 5.
[0138] Table 5
[0139]
[0140] In Example 1-3, a portion of silicon dioxide is specially treated and used together with specially treated titanium dioxide as a raw material component of a glass substrate to produce a glass substrate with a relatively thin thickness, thereby maintaining good optical properties, and having high visible light transmittance and total solar energy transmittance.
[0141] In the raw material components of Comparative Example 1, surface amino-treated silica is no longer added as a raw material component, but the same mass of matrix silica is used instead. Untreated silica will cause the optical properties of the glass to decrease, and the visible light transmittance and total solar energy transmittance will decrease more seriously;
[0142] In the raw material components of Comparative Example 2, modified titanium dioxide is no longer added as a raw material component, but untreated titanium dioxide of the same mass is used instead. Untreated titanium dioxide will cause a decrease in the optical properties of the glass, and both the visible light transmittance and the total solar energy transmittance will decrease to a large extent.
Claims
1. A low-brittle glass substrate, characterized in that: The raw material components of the glass substrate include base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, and the mass ratio of the components is 550-650:75-125:20-30:30-35:15-19:25-35:25-35:4-6; The preparation method of the surface amino-treated silicon dioxide comprises the following steps: controlling the heating rate to be 4.5-5.5°C / min, raising the temperature to 725-775°C, calcining the silicon dioxide for 350-370 minutes, naturally cooling to 68-72°C after the calcination is completed and keeping warm for standby use, adding the calcined silicon dioxide kept warm at 68-72°C to methanol at 68-72°C in a sealed container, stirring to mix evenly, then adding branched polyethyleneimine, keeping the temperature at 68-72°C, stirring for 23-25 hours, and after the stirring is completed, opening the sealed container, raising the temperature to 74-76°C to evaporate the methanol, and obtaining the surface amino-treated silicon dioxide; The mass ratio of the calcined silicon dioxide, methanol and branched polyethyleneimine is 45-55:100-120:0.9-1.1; The preparation method of the modified titanium dioxide comprises treating 3-aminopropyltriethoxysilane with polyglycolic acid, and modifying; The method for treating 3-aminopropyltriethoxysilane with polyglycolic acid comprises: mixing polyglycolic acid with acetone to completely dissolve the polyglycolic acid to obtain a polyglycolic acid solution; adjusting the pH of the polyglycolic acid solution to 2.3-2.5 with acetic acid; then adding 3-aminopropyltriethoxysilane; controlling the temperature to 1-3° C.; stirring; maintaining the pH at 5.4-5.6 during stirring; stirring for 50-70 min; evaporating the solvent after the stirring is completed; adding the obtained solid product to a sodium hydrosulfide aqueous solution; stirring for 40-50 min; filtering, washing, and drying the product after the stirring is completed to obtain polyglycolic acid-treated 3-aminopropyltriethoxysilane; The mass ratio of the polyglycolic acid, acetone and 3-aminopropyltriethoxysilane is 4.5-5.5:75-125:24-30; The mass ratio of the solid product to the sodium hydrosulfide aqueous solution is 1:4.5-5.5; The concentration of the sodium hydrosulfide aqueous solution is 4.5-5.5wt%; The modification method comprises the following steps: uniformly dispersing titanium dioxide in anhydrous ethanol, then adding polyglycolic acid treated 3-aminopropyltriethoxysilane, adjusting the pH to 3.6-3.8 with hydrochloric acid, controlling the temperature to 62-67° C., stirring for 4.5-5.5 hours, and after the stirring is completed, filtering, washing, and drying to obtain modified titanium dioxide; The mass ratio of the titanium dioxide, anhydrous ethanol and polyglycolic acid treated 3-aminopropyltriethoxysilane is 8-12:125-175:0.9-1.
1.
2. The low-brittle glass substrate according to claim 1, characterized in that: The purity of the matrix silicon dioxide is 99.79wt%, the iron content is 27ppm, the particle size is 35μm, and the specific surface area is 334m 2 / g.
3. The low-brittle glass substrate according to claim 1, characterized in that: In the preparation method of the surface amino-treated silica, the silica purity is 99.79wt%, the iron content is 27ppm, the particle size is 20μm, and the specific surface area is 327m 2 / g.
4. The low-brittle glass substrate according to claim 1, characterized in that: In the preparation method of the surface amino-treated silicon dioxide, the weight average molecular weight of the branched polyethyleneimine is 12700-13600 g / mol.
5. The low-brittle glass substrate according to claim 1, characterized in that: In the modification step of the preparation method of the modified titanium dioxide, the particle size of the titanium dioxide is 70 μm.
6. The process for preparing a low-brittle glass substrate according to claim 1, characterized in that: The preparation method of the glass substrate comprises the following steps: using a float process to prepare the glass substrate, mixing a specified mass of base silicon dioxide, surface amino-treated silicon dioxide, aluminum oxide, boron oxide, modified titanium dioxide, sodium oxide, magnesium oxide, and cerium oxide, ensuring that the components are evenly mixed, controlling the temperature to be 1520-1570° C., melting the melted glass liquid, passing the melted glass liquid through a tin bath, controlling the molding temperature in the tin bath to be 825-875° C., controlling the outlet temperature of the tin bath to be 630-650° C., performing float molding, exiting the tin bath after molding, annealing, and finally polishing the surface to obtain the glass substrate; The thickness of the glass substrate is 0.5 mm and the density is 2.33-2.34 g / cm 3 .
Citation Information
Patent Citations
High-stability long-service-life substrate glass for liquid crystal display
CN117105526A
Breakage-proof glass cup
CN114409255A
High-refraction wear-resistant glass bead and preparation process thereof
CN118459103A
Cited By
Glass substrate for packaging high-thermal-conductivity chip and preparation method of glass substrate
CN122608300A